Portuguese Intra-Industry Trade: A Dynamic Panel Data Analysis - Faustino, Horácio C. (2010)
This paper provides empirical evidence of the determinants of intra-industry trade (IIT), horizontal IIT and vertical IIT between Portugal and six European trading partners, using a dynamic panel data analysis. The paper introduces the distinction between the short-run and the long-run effects of the industry characteristics on IIT. The relationship between IIT and comparative advantages is also tested. The estimation results suggest that Portugal has comparative advantages in low-quality varieties and support Davis' (1995) hypothesis that decreasing costs are not necessary for IIT. The findings of the paper also provide an answer to Torstenson's (1996) question, namely that it is primarily human capital, rather than physical capital, that determines the quality of differentiated products.